Is Better Knowledge about Health Benefits of Dietary Fiber Related to Food Labels Reading Habits? A Croatian Overview - Ljubičić, Marija (2022)
The aim of this cross-sectional study was to determine the associations between health dietary patterns, knowledge, and consumption of dietary fiber (DF) with frequency of food label reading on food products with special reference to DF. The study was conducted in 2536 Croatian adults using an original questionnaire. Multiple linear regression models were used to assess associations between food label reading habits and predictor variables. Our study confirms the association between habits regarding the reading of labels on food products, especially in relation to information about DF with the sociodemographic factors of respondents, dietary food patterns and DF consumption, as well as knowledge and sources of information about DF. Women, individuals with a university-level education, and those living in an urban environment had more frequent labels used. Food habits as well as eating outside of the home were positive predictors while eating fast food was a negative predictor of food label reading. Knowledge about DF, especially about its health benefits, was also associated with food label reading. The interpretation of associations could help with the design of effective public health programs. Targeted education campaigns to educate and sensitize the population about food labeling and monitoring may improve general knowledge about healthy food and its benefits, which include indirect effects on the prevention of non-communicable chronic diseases.